Deskripsi Kemampuan Anak Usia Dini Di Kabupaten Kubu Raya Dalam Mengenal Bagian Tubuh Manusia Melalui Media Gambar - Miranda, Reni Marlina, Dian (Universitas Tanjungpura, 2017)
This study was aimed at identifying the preschool children’s (children aged 3 - 5) understanding on parts of the body. It covers the three compnents: 1) the ability to name parts of the body, 2) knowledge of the function of each part of the body named, and 3) the ability to explain how to take care of them. This descriptive study involved 105 preschoolers, as the sample with three criteria: 1) children aged 3 to 5 years old, 2) children without physical disability, and 3) children born in Kubu Raya. The instruments used were media images of the 23 parts of human body. The results showed that 100% of the children knew the eight parts of the body such as the eyes, hair, nose, ears, head, legs, stomach, and mouth. Likewise, the children completely (100%) recognize and know the way how to take care of the body parts. However, they still did not know some parts of the body i.e. the penis, ankles, vagina, upper arm, forearm and wrist, in terms of name, function, or the way to take care of.